Research Progress of Memory Mechanism in Cognitive Psychology - Wang, Luoyu (International Journal of Public Health and Medical Research, 2025)
Memory is a core problem in cognitive psychology and is crucial to understanding the acquisition, preservation and extraction of information. This study summarizes the dynamics of memory mechanisms, including theoretical evolution, systematic partitioning, process analysis, performance factors, barrier exploration, and clinical practice. Starting with the basic concept of memory and its importance in psychology, this paper reviews the background and value of memory research, and makes an in-depth study of classical and modern memory models to deepen the understanding of memory operation. Types of memories, such as instantaneous, persistent, unconscious, and conscious, are distinguished, with emphasis on encoding, retention, extraction, and fading. This paper discusses the biological, psychological, sociocultural, and environmental factors that influence memory, and highlights advances in the study of memory disorders, interdisciplinary collaboration, and neuroimaging. It concludes with a summary of the findings and future directions, including personalized memory enhancement and contributions to education, healthcare, and social development. This study deepens the understanding of memory mechanism and has practical guiding significance.